Patients with IVF complicated by moderate-to-critical OHSS experience increased thrombosis, GDM and neonatal NICU admission but slightly shorter gestation compared with matched IVF counterparts: A retrospective Chinese cohort study - Linli Hu; Rui Xie; Mengying Wang; Yingpu Sun (BMC, 2021)
Abstract Background Ovarian hyperstimulation syndrome (OHSS) is a common disease during controlled ovarian hyperstimulation treatment. However, the obstetric and neonatal outcomes of this group of patients are unknown. The aim of this study was to explore the effects of late moderate-to-critical OHSS on obstetric and neonatal outcomes. Methods This prospective observational study included 17,537 patients who underwent IVF/ICSI-fresh embryo transfer (ET) between June 2012 and July 2016 and met the inclusion criteria, including 7,064 eligible patients diagnosed with clinical pregnancy. Ultimately, 6,356 patients were allocated to the control group, and 385 patients who were hospitalized and treated at the center for late moderate-to-critical OHSS were allocated to the OHSS group. Then, propensity score matching analysis was performed, matching nine maternal baseline covariates and the number of multiple gestations; 385 patients with late moderate-to-critical OHSS were compared with a matched control group of 1,540 patients. The primary outcomes were the live birth rate, preterm delivery rate, miscarriage rate, gestational age at birth (weeks), obstetric complications and neonatal complications. Results The duration of gestation in the matched control group was significantly higher than that in the OHSS group. The live birth delivery rate did not significantly differ between the OHSS and matched control groups. The incidence rates of the obstetric complications venous thrombosis (VT) and gestational diabetes mellitus (GDM), neonatal complications and the number of neonates admitted to the NICU were significantly higher in the OHSS group than in the matched control group. Conclusions Pregnant women undergoing IVF with fresh ET whose course is complicated by late moderate-to-critical OHSS appear to experience shortened gestation and increased obstetrical and neonatal complications compared with matched controls whose course is not complicated by OHSS. However, the live birth rate, average neonatal weight, and incidence rates of premature delivery, miscarriage, early abortion, hypertensive disorder of pregnancy (HDP), placenta previa (PP), intrahepatic cholestasis of pregnancy (ICP), and low neonatal birth weight (LBW) did not differ significantly between the two groups.